Carious lesion management in children and adolescents by Australian dentists. (8th August 2019) - Keys, T; Burrow, MF; Rajan, S; Rompre, P; Doméjean, S; Muller‐Bolla, M; Manton, DJ
Abstract: Background: The management of carious lesions in children and adolescents can have lifelong implications for the patient. The aim of this study was to assess the decision‐making process of dentists when managing carious lesions in children and adolescents. Methods: Approximately, 11 000 dentists listed as members of the Australian Dental Association Inc. (ADA) and Australian and New Zealand Society of Paediatric Dentistry (ANZSPD) were emailed a link in April 2017 to a 19‐question survey delivered by SurveyMonkey™. Results: In this study, 887 responses were received. In 'enamel‐limited' carious lesions, dentists intervened most frequently in primary tooth approximal (365, 41.1%), followed by permanent tooth occlusal (295, 33.3%) and approximal (244, 27.5%), and primary tooth occlusal (203, 22.9%) surface carious lesions. Age, university of graduation, practicing state, decade of graduation and frequency of treatment of children between 6 and 15 years were significant demographic factors influencing the restorative threshold. Conclusions: Australian dentists reported significant variation in their management of approximal and occlusal carious lesions in both primary and permanent teeth. A substantial proportion of respondents would intervene surgically on non‐cavitated enamel‐limited lesions.